Gottschalk and a medieval predestination controversy : texts translated from the Latin - Gottschalk, of Orbais, ca. 803-ca. 867. (Mediaeval philosophical texts in translation ;, 2010)
The question of predestination and its nature, which drew strong protests from the monks of Provence in the early fifth century against the teaching of Augustine of Hippo, was initially settled by the Council of Orange in 529. But in the Carolingian renaissance in the ninth century, the Benedictine monk, Gottschalk of Orbais, brought the teachings of the late Augustine to the forefront of theological debate and greatly disturbed the clergy and faithful with his doctrine of double predestination of some to the joy of heaven and of others to the eternal punishment of hell -- a doctrine that he claimed was that of Augustine and the Catholic faith. The present volume provides for the first time an English translation of Gottschalk's key writings on predestination and various reactions and comments from leading theologians of the ninth century, as well as a learned introduction to Gottschalk's life and controversies. - Publisher.